Corporate governance through an audit committee: an empirical study - Lal Bhasin, M.; Shaikh, Junaid (www.Inderscience.com, 2012)
Even though there are many measures to put corporate governance (CG) in place and practise, an important tool essential for the success is the efficacy and effective functioning of an audit committee (AC). Nowadays, an AC is being looked upon as a distinct culture for CG and has received wide-publicity across the globe. Government authorities, regulators and international bodies all have indicated that they view an AC as a potentially powerful tool that can enhance the reliability and transparency of financial information. Being mandatory under SEBI's clause 49 of the listing agreement, an AC can be of great help to the board in implementing, monitoring and continuing 'good' CG practises to the benefit of the corporation and all its stakeholders. This study performs a 'content' analysis on the AC reports of the top 500 listed companies in India during 2005 to 2008 to determine the information content of these reports and the extent to which these reports conform to the clause 49 requirements of the SEBI. Also, discussed are the various trends about an AC characteristics viz., size, composition, activity, as well as the extent of non-audit services provided by auditors in the top 500 listed Indian companies.